Epidural Blockade Modifies Perioperative Glucose Production without Affecting Protein Catabolism - Lattermann, Ralph; Carli, Franco; Wykes, Linda; Schricker, Thomas (Anesthesiology (Philadelphia), 2002)
Epidural blockade with local anesthetic has been shown to blunt the increase in plasma glucose concentration during and after abdominal surgery. The aim of the study was to test the hypothesis that epidural blockade inhibits this hyperglycemic response by attenuating endogenous glucose production. The authors further examined if the modification of glucose production by epidural blockade has an impact on perioperative protein catabolism. Sixteen patients undergoing colorectal surgery received either general anesthesia and epidural blockade with local anesthetic (n = 8) or general anesthesia alone (control, n = 8). Glucose and protein kinetics were assessed by stable isotope tracer technique ([6,6-2H2]glucose, L-[1-13C]leucine) during and 2 h after surgery. Plasma concentrations of glucose, lactate, free fatty acids (FFA), cortisol, glucagon, and insulin were also determined. Epidural blockade blunted the perioperative increase in the plasma concentration of glucose, cortisol, and glucagon when compared with the control group (P < 0.05). Plasma concentrations of lactate, FFA, and insulin did not change. Intra- and postoperative glucose production was lower in patients with epidural blockade than in control subjects (intraoperative, epidural blockade 8.2 +/- 1.9 vs. control 10.7 +/- 1.4 micromol x kg(-1) x min(-1), P < 0.05; postoperative, epidural blockade 8.5 +/- 1.8 vs. control 10.5 +/- 1.2 micromol x kg(-1) x min(-1), P < 0.05), whereas glucose clearance decreased to a comparable extent in both groups (P < 0.05). Protein breakdown (P < 0.05), protein synthesis (P < 0.05), and amino acid oxidation (P > 0.05) decreased with both anesthetic techniques. Epidural blockade attenuates the hyperglycemic response to surgery through modification of glucose production. The perioperative suppression of protein metabolism was not influenced by epidural blockade.